2014
DOI: 10.6061/clinics/2014(02)01
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured transdermal hormone replacement therapy for relieving menopausal symptoms: a confocal Raman spectroscopy study

Abstract: OBJECTIVE:To determine the safety and efficacy of a transdermal nanostructured formulation of progesterone (10%) combined with estriol (0.1%) + estradiol (0.25%) for relieving postmenopausal symptoms.METHODS:A total of 66 postmenopausal Brazilian women with climacteric symptoms of natural menopause received transdermal nanostructured formulations of progesterone and estrogens in the forearm daily for 60 months to mimic the normal ovarian secretory pattern. Confocal Raman spectroscopy of hormones in skin layers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 12 publications
3
29
0
3
Order By: Relevance
“…The efficacy of MNPEE in reducing the frequency of hot flushes was significantly higher than that of placebo at from weeks three to 12. At the 12 th week, MNPEE could decrease the daily frequency of hot flushes by 11.1 times Botelho, 2014 [21] Title: Nanostructured transdermal hormone replacement therapy for relieving menopausal symptoms: a confocal Raman spectroscopy study Type of study: Long-term clinical trial Participants: 66 postmenopausal women with climacteric syndrome Study design: In order to provide a hormone secretion pattern similar to that of normal ovaries, the participants were asked to apply transdermal nanostructured progesterone and estrogen formulations on their forearms every day for 60 months. The assessment of hormones in different skin layers was conducted using confocal Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The efficacy of MNPEE in reducing the frequency of hot flushes was significantly higher than that of placebo at from weeks three to 12. At the 12 th week, MNPEE could decrease the daily frequency of hot flushes by 11.1 times Botelho, 2014 [21] Title: Nanostructured transdermal hormone replacement therapy for relieving menopausal symptoms: a confocal Raman spectroscopy study Type of study: Long-term clinical trial Participants: 66 postmenopausal women with climacteric syndrome Study design: In order to provide a hormone secretion pattern similar to that of normal ovaries, the participants were asked to apply transdermal nanostructured progesterone and estrogen formulations on their forearms every day for 60 months. The assessment of hormones in different skin layers was conducted using confocal Raman spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Botelho et al reported the use of nanoparticles in transdermal HRT as a safe and efficient controlled drug release system to alleviate menopausal symptoms [21]. In another study, Botelho et al evaluated the efficacy of a novel transdermal delivery system using a nanostructured formulation containing testosterone and progesterone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 This new technology is present in many fields in medical science and it has been proving to be a strong allied with unique properties for drugs delivery and physiologic absorption. 10,11 Over the years, there has been an increasing interest regarding the determination of which symptoms could be used to precisely define testosterone deficiency in women.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Is it well established that postmenopausal women continue to be sexually active despite sexual complaints. [2][3][4][5][6][7][8][9][10][11][12][13] Sexual activity is a useful tool to maintain a healthy life. Women were allocated to this study if they reported significant loss of sexual desire.…”
mentioning
confidence: 99%